2004
DOI: 10.1111/j.1365-2648.2004.02982.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nurses in physician‐assisted dying

Abstract: Nurses in Belgium are largely involved in administering lethal drugs in end-of-life decisions, while their participation in the decision-making process is rather limited. To guarantee prudent practice in end-of-life decisions, we need clear guidelines, professionally supported and legally controlled, for the assignment of duties between physicians and nurses regarding the administration of lethal drugs to reflect current working practice. In addition, we need appropriate binding standards governing mutual comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 22 publications
3
76
0
4
Order By: Relevance
“…As confirmed by international literature (11,17,18,25,26), DNR decisions are mostly made late in the course of the disease and the most important reasons for such decisions are disease-related. Age of the patient is only mentioned as a reason in combination with the underlying condition of the patient.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As confirmed by international literature (11,17,18,25,26), DNR decisions are mostly made late in the course of the disease and the most important reasons for such decisions are disease-related. Age of the patient is only mentioned as a reason in combination with the underlying condition of the patient.…”
Section: Discussionmentioning
confidence: 85%
“…Nurses are most frequently consulted in decision-making, probably because they care for the patient on a daily basis and often have a confidential and close relationship with the patient and his or her next of kin (26). Almost all DNR decisions (93.7%) were shared with the nursing team via the patient's file, which minimizes inappropriate CPR (14,27).…”
Section: Discussionmentioning
confidence: 99%
“…6 However, physicians worldwide have reported that nurses are also involved in these medical practices, mostly in the decision-making and sometimes in the administration of the life-ending drugs. [1][2][3][7][8][9] Critical care, 10 oncology 11 and palliative care nurses 12,13 have confirmed this by reporting their own involvement, particularly in cases of euthanasia. 14,15 In Belgium, the law permits physicians to perform euthanasia under strict requirements of due care, one of which is that they must discuss the request with the nurses involved.…”
mentioning
confidence: 63%
“…7,9,17,22 Nevertheless, uncertainty remained about the understanding by the nurses of the act that they performed. In our study, nurses did administer life-ending drugs with the recognition that the death of the patient was intended.…”
Section: Researchmentioning
confidence: 99%
“…Research in countries with legislation on assisted dying shows that nurses play a variety of decisive roles in the context of assisted dying. [12][13][14][15] But the debate is suffering from a division in ''pro'' and ''contra'' camps with the result that a consensus on values and best practices is far from being reached. 16 Leaving aside the issue whether such a consensus is necessary for responding effectively to the needs of patients, the question remains if healthcare professions have a specific voice in this regard.…”
mentioning
confidence: 99%